Multidisciplinary management of difficult/aggressive growth-hormone pituitary neuro-endocrine tumors - Bianchi, Antonio; Chiloiro, Sabrina; Giampietro, Antonella; Gaudino, Simona; Calandrelli, Rosalinda; Mazzarella, Ciro; Caldarella, Carmelo; Rigante, Mario; Gessi, Marco; Lauretti, Liverana; De Marinis, Laura; Olivi, Alessandro; et al. (Frontiers in Endocrinology, 2023)
Acromegaly is defined as difficult or aggressive in patients with growth hormone-secreting neuroendocrine tumors that require multiple surgeries and medical treatments to achieve disease control. To date, there are no clinical, laboratory, molecular, or and neuroradiological markers that are able to univocally predict disease prognosis in patients with acromegaly. Therefore, the management of these patients requires careful evaluation of laboratory assessments, diagnostic criteria, neuroradiology examinations, and neurosurgical approaches to choose an effective and patient-tailored medical therapy. A multidisciplinary approach is particularly useful in difficult/aggressive acromegaly to schedule multimodal treatment, which includes radiation therapy, chemotherapy with temozolomide and other, recent emerging treatments. Herein, we describe the role of the different members of the multidisciplinary team according to our personal experience; a flow-chart for the therapeutic approach of difficult/aggressive acromegaly patients is proposed.